The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2019
DOI: 10.3889/oamjms.2019.587
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Pregnancy Outcomes at Advanced Maternal Age

Abstract: AIM: The study aimed to investigate the association between advanced maternal age (AMA) and the risk of adverse maternal, perinatal and neonatal outcomes about parity in singleton pregnancies.METHODS: We retrospectively analysed 950 women who gave birth in the Department of Obstetrics and Perinatology of the University Hospital in Kraków for six months (between 1st January and 30th June 2018). The patients were divided into 3 groups according to their age (30-34 years old, 35-39 years old and over 40 years old… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

9
16
4

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 32 publications
(32 citation statements)
references
References 23 publications
9
16
4
Order By: Relevance
“…In our group of 563 participants (in the current analysis), the frequency of the pregnancy outcomes (8.4% of the deliveries were <37th week; 8.5% of the women gave birth to newborn <10th percentile, and 11.4% gave birth to newborn >90th percentile) was close to the frequency in other Polish studies [43,44]. In our analysis, the frequency of main complications (21.3% of the women have developed PIH and 19.5% have developed GDM) was about 2-4 times higher compared to the frequency in several Polish studies [43,45,46]. At the same time, among our participants, 40.7% of the women were primiparous, 39.1% had prepregnancy BMI ≥25 kg/m 2 , and 63.6% were ≥35 years.…”
Section: Discussionsupporting
confidence: 81%
“…In our group of 563 participants (in the current analysis), the frequency of the pregnancy outcomes (8.4% of the deliveries were <37th week; 8.5% of the women gave birth to newborn <10th percentile, and 11.4% gave birth to newborn >90th percentile) was close to the frequency in other Polish studies [43,44]. In our analysis, the frequency of main complications (21.3% of the women have developed PIH and 19.5% have developed GDM) was about 2-4 times higher compared to the frequency in several Polish studies [43,45,46]. At the same time, among our participants, 40.7% of the women were primiparous, 39.1% had prepregnancy BMI ≥25 kg/m 2 , and 63.6% were ≥35 years.…”
Section: Discussionsupporting
confidence: 81%
“…The analysis of our results requires highlighting a few facts. The frequency of all PIH cases in our cohort ( n = 137 = 15.0%) is 2–3 times higher than in other Polish studies [ 26 , 27 ]. The probable reason for this is the fact that the study was performed in a third-degree reference center, where women with risk factors report for additional tests.…”
Section: Discussioncontrasting
confidence: 68%
“…In this study, mothers aged 35 were one of the contributing factors to birth asphyxia rates. The following discovery was very nearly found to be a universal fact: the increased age of the mother increased the risk of several adverse outcomes [32][33][34]. Similar findings were also reported from a study carried out in Cameroon [20] which revealed that mothers aged 35 were more likely to experience a birth asphyxia.…”
Section: Discussionsupporting
confidence: 61%